Previously Unidentified Gene Variation Associated with Fabry Disease: The Impact on One Family - Amaresh R. Vanga; Samantha A. Schrier Vergano; Jolanta Kowalewska; Thomas R. McCune (Case Reports in Nephrology)
Fabry disease is an X-linked lysosomal storage genetic disorder associated with over 1000 mutations in the alpha-galactosidase-A gene region. We report here a 69-year-old male who underwent a kidney biopsy to evaluate progressive renal failure. He was found to have zebra bodies in visceral epithelial cells on biopsy, with electron microscopy showing inclusions within the cytoplasm of multiple podocytes consistent with Fabry disease. An alpha-galactosidase level was found to be 21 nm/hr/mg (normal range 50–150 nm/hr/mg). Genetic studies revealed a missense variant in the GLA gene with alanine replaced by cysteine at position 682 (c.682 A > C, p.N228H) that had not been previously associated with Fabry disease. The same variant was detected in two additional family members. The pathologic findings, clinical features, and low alpha-galactosidase level suggest that the c.682 A > C variant is associated with Fabry disease.